Queensland Aboriginal and Torres Strait Islander food and nutrition strategy. - Queensland Health; Australian Centre for International and Tropical Health and Nutrition ([Brisbane] : Queensland Health, 1995)
Framework for the provision of planning, and co-ordination of action on Aboriginal and Torres Strait Islander nutrition in Queensland; identification of key issues - infrastructure and workforce development, community programs; guidelines for the allocation of resources and implementation strategies.
"... prepared by the Indigenous Health Program and Nutrition Program, Australian Centre for International and Tropical Health and Nutrition, (ACITHN), University of Queensland." -- acknowledgements.
Keywords: Aboriginal Australians -- Queensland -- Food; Aboriginal Australians -- Queensland -- Nutrition; Health - Policy and administration; Health status - Nutrition; Queensland (Qld)